Identificação de vazamento em redes de distribuição de água por meio de algoritmo genético com dados transientes - Alexandre, Adriano Ricardo Almeida (2005)
A great present problem in the nets of distribution of water in the World is the presence of index of losses, whose considerable portion elapses of the presence of physical losses, tends as the largest component the leaks. These leaks cause not only operational and financial difficulties, as well as waste of this limited natural resource. It constitutes goal in the modern society the decrease of this it records problem. The present work approaches the theme and it proposes a methodology of study of a detection technique and quantification of leaks in distribution nets by of the modeling of this parameter. The employed method in the solution of the inverse problem is the use of data transients for calibration of the parameter leak through the genetic algorithm. In the analysis of the phenomenon transient, the Method of the Characteristics is used. A net example is used to study the identification of leaks and to evaluate the reliability of the method. Several results were presented and discussed with the application of this method in different situations and compared the results obtained by the genetic algorithm with the previous knowledge of the conditions permanent initials and without the use of this knowledge.